Risks management in rural tourism - Štetić, Snežana (Economics of Agriculture, 2010)
Tourism today presupposes an integrated quality of facilities and services for its development, as well as the total quality of tourism products offered to consumers. The risks that arise in every step of creation, promotion, presentation, marketing and sales of rural products have a constant influence on the growth and development of rural tourism market. People create the needs not only considering the change in life and learning about other cultural goods, but also the need for isolation in order to achieve better health, psycho-physical state and stability. Regions that attract many tourists are rural areas. Rural areas could be classifed in the category, as well as ecological and protected areas and places that can meet cultural and recreational needs of a visitor As we know, tourism is sensitive to all negative phenomena in the natural environment, as well as in social events. In the era of terrorism, global warming, natural disasters and hostilities that govern the world we have to understand that the time of safety and security is the past. Therefore, for the development of tourism in rural destination it is extremely important to envisage all the weaknesses that occur in the feld of safety and security.